PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT VARA SUJANA ADHI PARAMITA (KING’S FUN) JAKARTA BARAT - Nurgianto, Anani; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2023)
The purpose of this research is to determine the effect of work stress on performance, the work environment on performance and to determine the effect of work stress and the work environment on employee performance at PT Vara Sujana Adhi Paramita (King's Fun) in West Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 60 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this research are that work stress has a significant effect on employee performance. This is proven by the regression equation Y = 27.568 + 0.342 The work environment has a significant effect on employee performance, this is proven by the regression equation Y = 25.798 + 0.397 Work stress and the work environment simultaneously have a significant effect on employee performance with the regression equation Y = 26.350 – 0.070X1 + 0455X2. The coefficient of determination value was 31.6% while the remaining 68.4% was influenced by other factors that were not researched. Hypothesis testing obtained a value of Fcount > Ftable or (16.585 > 2.761). Thus, work stress and the work environment together have a positive and significant influence on employee performance at PT Vara Sujana Adhi Paramita (King's Fun) in West Jakarta.